Constraining quenching time-scales in galaxy clusters by forward-modelling stellar ages and quiescent fractions in projected phase space. Issue 2 (13th April 2023) - Reeves, Andrew M M; Hudson, Michael J; Oman, Kyle A
ABSTRACT: We forward-model mass-weighted stellar ages (MWAs) and quiescent fractions ( f Q ) in projected phase space (PPS), using data from the Sloan Digital Sky Survey, to jointly constrain an infall quenching model for galaxies in log ( M vir /M⊙ ) > 14 galaxy clusters at z ∼ 0. We find the average deviation in MWA from the MWA– M ⋆ relation depends on position in PPS, with a maximum difference between the inner cluster and infalling interloper galaxies of ∼1 Gyr. Our model employs infall information from N -body simulations and stochastic star-formation histories from the universemachine model. We find total quenching times of t Q = 3.7 ± 0.4 Gyr and t Q = 4.0 ± 0.2 Gyr after first pericentre, for 9 < log ( M ⋆ /M⊙ ) < 10 and 10 < log ( M ⋆ /M⊙ ) < 10.5 galaxies, respectively. By using MWAs, we break the degeneracy in time of quenching onset and time-scale of star formation rate (SFR) decline. We find that time of quenching onset relative to pericentre is t_delay=3.5^+0.6_-0.9 Gyr and t_delay=-0.3^+0.8_-1.0 Gyr for 9 < log ( M ⋆ /M⊙ ) < 10 and 10 < log ( M ⋆ /M⊙ ) < 10.5 galaxies, respectively, and exponential SFR suppression time-scales are τenv ≤ 1.0 Gyr for 9 < log ( M ⋆ /M⊙ ) < 10 galaxies and τenv ∼ 2.3 Gyr for 10 < log ( M ⋆ /M⊙ ) < 10.5 galaxies. Stochastic star formation histories remove the need for rapid infall quenching to maintain the bimodality in the SFR of cluster galaxies; the depth of the green valley prefers quenching onsets close to first pericentre and a longer quenching envelope, in slight tension with the MWA-driven results. Taken together these results suggest that quenching begins close to, or just after pericentre, but the time-scale for quenching to be fully complete is much longer and therefore ram-pressure stripping is not complete on first pericentric passage.